Research on comprehensive evaluation method of distribution network based on AHP-entropy weighting method - Liu, ZiWei; Xie, QiongYao; Dai, Lu; Wang, HaiLiang; Deng, Ling; Wang, Chun; Zhang, Yu; Zhou, XiaoXia; Yang, ChuYuan; Xiang, Chuan; Qin, SiYu (Frontiers in Energy Research, 2022)
In the context of smart grid planning and construction, how to tackle the future distribution network, a com-prehensive evaluation of smart distribution network planning has become an urgent problem to be solved. To address this issue, this research provides a method for comprehensive evaluation that combines subjective and objective weighing approaches. Firstly, a set of evaluation index system is constructed and quantified based on the characteristics of the future distribution network; after that a comprehensive evaluation model is established and a subjective and objective weighting method combining AHP-entropy weighting method is used to weight the indicators; Finally,the actual data from the distribution network is evaluated and scored. Based on the scoring verification results, the correct-ness and effectiveness of the method proposed in this paper are verified.